Natural plant fibers obtained from agricultural residue used as an ingredient in food matrixes or packaging materials: A review - Soleimanian, Yasamin; Sanou, Ibrahima; Turgeon, Sylvie L.; Canizares, Diego [UNESP]; Khalloufi, Seddik (Wiley, 2022)
Every year, agrifood activities generate a large amount of plant byproducts, which have a low economical value. However, the valorization of these byproducts can contribute to increasing the intake of dietary fibers and reducing the environmental pollution. This review presents an overview of a wide variety of agricultural wastes applied in the formulation of different food products and sustainable packaging. In general, the incorporation of fibers into bakery, meat, and dairy products was successful, especially at a level of 10% or less. Fibers from a variety of crops improved the consistency, texture, and stability of sauce formulations without affecting sensory quality. In addition, fiber fortification (0.01–6.4%) presented considerable advantages in terms of rheology, texture, melting behavior, and fat replacement of ice cream, but in some cases had a negative impact on color and mouthfeel. In the case of beverages, promising effects on texture, viscosity, stability, and appetite control were obtained by the addition of soluble dietary fibers from grains and fruits with small particle size. Biocomposites used in packaging benefited from reinforcing effects of various plant fiber sources, but the extent of modification depended on the matrix type, fiber pretreatment, and concentration. The information synthesized in this contribution can be used as a tool to screen and select the most promising fiber source, fiber concentration, and pretreatment for specific food applications and sustainable packaging.